2007
DOI: 10.1111/j.1520-037x.2007.06556.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Quinapril in the Presence of a Weight Loss Regimen: Endothelial Function and Markers of Obesity in Patients With the Metabolic Syndrome

Abstract: Forty-four patients with the metabolic syndrome were placed on a reduced-calorie and reduced-fat regimen to lose weight throughout a 56-week period. The patients were treated in a crossover fashion with placebo and the angiotensin-converting enzyme inhibitor quinapril for 24 weeks each. The study measured endothelial-dependent flow-mediated dilation plus serum obesity markers of adiponectin and leptin. Metabolic parameters improved after 56 weeks. Serum adiponectin level increased by 18% (P<.05 vs baseline) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
1
10
0
1
Order By: Relevance
“…A later study on weight loss by reduced-calorie and reduced-fat regimen for about 6 months confirmed this leptin-lowering effect. 23 In a 3-month treatment for obesity-related hypertension, ACE inhibitors together with calcium channel blockers were able to support the weight-reducing actions and concomitant metabolic changes induced by sibutramine. 24 However, in these human studies, no information on the effect of ACE inhibitors per se on the weight loss and/or maintenance has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A later study on weight loss by reduced-calorie and reduced-fat regimen for about 6 months confirmed this leptin-lowering effect. 23 In a 3-month treatment for obesity-related hypertension, ACE inhibitors together with calcium channel blockers were able to support the weight-reducing actions and concomitant metabolic changes induced by sibutramine. 24 However, in these human studies, no information on the effect of ACE inhibitors per se on the weight loss and/or maintenance has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…These include ethnic groups such as African Americans, patients with obesity, and patients with renal disease, metabolic syndrome, diabetes mellitus, and/ or existing vascular disease. Improvement in inflammatory and other biomarkers has been reported with ARBs and ACE inhibitors in patients with obesity and metabolic syndrome [Nagamia et al 2007;Sola et al 2005] and in patients with hypertension with and without type 2 diabetes mellitus (T2DM) [Derosa et al 2010;Persson et al 2006]. Similarly, calcium channel blockers (CCBs) have been shown to improve markers of inflammation in patients with hypertension [Komoda et al 2010;ShurtzSwirski et al 2006], while b-blockers such as nebivolol were shown to modify markers of inflammation and obesity in African Americans with obesity and hypertension [Merchant et al 2010].…”
Section: Introductionmentioning
confidence: 97%
“…These include ethnic groups such as African Americans, obese patients, and patients with renal disease, metabolic syndrome, diabetes mellitus, and/or existing vascular disease. Improvements in inflammatory and other biomarkers has been reported with ARBs and ACEIs in obese patients with metabolic syndrome [7,8] and in hypertensive patients with and without type 2 diabetes mellitus (T2DM) [9,10]. Similarly, CCBs have been shown to improve markers of inflammation in patients with hypertension [11,12], while -blockers such as nebivolol were shown to modify markers of inflammation and obesity in obese African Americans with hypertension [13].…”
Section: Introductionmentioning
confidence: 99%